PIOMETRA ABERTA EM FÊMEA FELINA: RELATO DE CASO - Silva, Tanara Raquel De Oliveira Da; Beck, Cristiane; Teichmann, Cristiane Elise; Fraga, Denize Da Rosa; Pereira, Roberta Carneiro Da Fontoura (Salão do Conhecimento, 2019)
Projeto de extensão realizado no curso de Medicina Veterinária da Unijuí